2000
DOI: 10.1046/j.1365-2133.2000.03836.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the sensitivity for melanoma diagnosis by primary care physicians using skin surface microscopy

Abstract: All PCP in countries where melanoma leads to significant mortality should be trained in skin surface microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
1
5

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(148 citation statements)
references
References 30 publications
9
133
1
5
Order By: Relevance
“…Use of dermoscopy as a triage tool for suspicious lesions has been advocated 42 . The Three-Point Checklist, a dermoscopic algorithm (described in the Online Appendix), has been shown to improve the ability of PCPs to triage suspicious lesions 40,[43][44][45][46][47] . Several studies have demonstrated improved diagnostic accuracy when teaching dermoscopy to nondermatologists, supporting that dermoscopy may be a valuable addition to a skin cancer education curriculum 44,47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Use of dermoscopy as a triage tool for suspicious lesions has been advocated 42 . The Three-Point Checklist, a dermoscopic algorithm (described in the Online Appendix), has been shown to improve the ability of PCPs to triage suspicious lesions 40,[43][44][45][46][47] . Several studies have demonstrated improved diagnostic accuracy when teaching dermoscopy to nondermatologists, supporting that dermoscopy may be a valuable addition to a skin cancer education curriculum 44,47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Westerhoff et al's RCT evaluated an educational intervention for improving melanoma diagnosis using Intervention did decrease the surface microscopy. 31 The control group did not receive the training. Participants' diagnostic ability on clinical photographs was found to significantly improve in those who had received the microscopy training.…”
Section: Intervention Typementioning
confidence: 99%
“…Some studies had a high risk of selection bias, [13][14][15][16][17]19,20,22,24,25,27,[29][30][31] with little information given (if any) about whether those who participated were different from those who chose not to take part. Almost all studies reported a follow-up period of less than 1 year; 11,14,[17][18][19]21,23,24,27,28,31,33 several tested participants straight after the intervention; 15,16,29,30 and some did not include or state any follow-up period. 20,22,25,32 Therefore, it cannot be determined whether any of the reported improvements persisted.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Further, the gradual introduction of dermatoscopy in general practice may help here as suggested in several studies [15,16]. One issue is to which extent the study populations are representative for GP and academic melanomas.…”
Section: Discussionmentioning
confidence: 99%